Ortho-oxygenative 1,2-difunctionalization of diarylalkynes under merged gold/organophotoredox relay catalysis - Sancheti, Shashank P.; Akram, Manjur O.; Roy, Rupam; Bedi, Vaibhav; Kundu, Shubhankar; Patil, Nitin T. (Chemistry-An Asian Journal, 2019)
Reported herein is an ortho-oxygenative 1,2-difunctionalization of diarylalkynes under merged gold/organophotoredox catalysis to access highly functionalized 2-(2-hydroxyaryl)-2-alkoxy-1-arylethan-1-ones. Detailed mechanistic studies suggested a relay process, initiating with gold-catalyzed hydroalkoxylation of alkynes, to generate enol-ether followed by a key formal [4+2]-cycloaddition reaction. The successful application of the present methodology was also shown for the synthesis of benzofurans.
Keywords: binary catalyst system; Gold catalysis; organocatalyst; photoredox; synthetic methodology

Phosphine radical cation catalysis for Markovnikov hydroamination of unactivated alkenes - Das, Nirmal; Barsu, Nagaraju (Journal of Chemical Sciences, 2026)
Markovnikov-selective hydroamination of unactivated terminal alkenes has long remained a challenging transformation in C-N bond formation. Fan and co-workers1 addressed this using a metal-free phosphine photoredox system that operates via an unprecedented phosphine radical cation (P(IV)) mechanism, enabling alkene activation toward azole addition. This work highlights a powerful new strategy for C(sp3)-N bond construction beyond traditional transition-metal catalysis.Graphical abstractMetal-free phosphine photoredox catalysis enables Markovnikov-selective hydroamination of unactivated terminalalkenes via a novel phosphine radical cation mechanism, off ering a new strategy for C(sp3)-N bond formation.
Keywords: azoles; hydroamination; Markovnikov selectivity; Phosphine catalysis; photoredox; radical cation